EVALUATION OF THE EFFECTIVENESS OF ENDOVASCULAR INTERVENTIONS IN PATIENTS WITH ACUTE CORONARY SYNDROME - Makhmudova M.M; Vinokurova E. S (Western European Studies, 2025)
The evaluation of the effectiveness of endovascular interventions in patients with acute coronary syndrome (ACS) is a key aspect of modern cardiology. It is based on clinical observation data, instrumental studies, and patient outcomes. The aim of this study was to assess the effectiveness of various endovascular interventions (EVI) in patients with acute coronary syndrome (ACS)
Keywords: syndrome; effectiveness; endovascular